Pendekatan Sirkuler dalam Kajian Perbandingan Mazhab - Jabbar Sabil (Media Syari'ah, 2017)
The study of Islamic law in the context of the comparative madhab is based on the plurality of truthful values. However, this study is frequently done with less appropriated approach, so that it is contradicted to the value. Therefore, this paper offers an approach that can objectify the value, namely the circular approach. In conducting this study, the philosophy as a method was used. As a philosophical fundamental structure, this paper refers to postmodern theory: that the knowledge is a prehension rather than an evidence. Therefore, the differences of opinion are considered as natural characters, as a result of geographical differences and human primordiality. In line with this matter, Fiqh is normally used to respond the legal issues in differences in allparts of the world. From systemic theory perspective, differences of opinion within the different mazhabs, therefore, become complementary. From this study, it is found that the circular approach can lead researchers to the awareness: the existence of mutual relations among the opinions of mazhab jurists.